Assessment of the Potential of Trichoderma spp. Strains Native to Bagua (Amazonas, Peru) in the Biocontrol of Frosty Pod Rot (Moniliophthora roreri) - Santos Leiva; Manuel Oliva; Elgar Hernández; Beimer Chuquibala; Karol Rubio; Flor García; Magdiel Torres de la Cruz (Agronomy, 2020)
The use of native Trichoderma strains has been proposed as a sustainable alternative to control cocoa diseases. The aim of this study was to assess indigenous Trichoderma strains from Bagua Province, Peru, with reference to their antagonistic characteristics in vitro and their potential for in vitro biocontrol against frosty pod rot (FPR) disease. A total of 199 strains were assessed for in vitro mycoparasitism, antibiosis, and potential antagonism. The effect of four strains was evaluated in vitro using epidemiological variables, yield, and efficacy at two sites (Copallín and La Peca). Significant differences (p < 0.05) were reported for all variables evaluated in vitro and in vitro. Mycoparasitism ranged from 32% to 100%, antibiosis from 33.36% to 57.92%, and potential antagonism from 42.36% to 78.64%. All strains were found to affect the in vitro-assessed parameters in addition to enhancing the productive yield. The efficiency ranged from 38.99% to 71.9% in Copallín, and 45.88% to 51.16% in La Peca. The CP24-6 strain showed the highest potential for biocontrol under field conditions when considering its effect on both sites.